Assessment of Public Compliance with Development Control Regulations in Auchi, Edo State, Nigeria - Daniel Nosakhare Onaiwu (The Indonesian Journal of Planning and Development, 2020)
The spatial structure of modern settlements is organized based on development control. The compliance of urban residents with development control regulations makes it possible for cities to be well structured for physical, aesthetic, and economic developments. The study aims to assess public compliance with development control in Auchi. A sample of 378 residents of Auchi was used in the study. The study area was divided into six strata, and samples were selected from the strata based on their population sizes. The instrument was a 5-point Likert-type option, which was administered to the respondents. The findings revealed that there was low compliance with development control standards in Auchi. There was awareness of developers on compliance but did not translate into compliance. The building coverage specified by development control regulations was grossly violated. There was a medium correlation (0.55) between education and level of non-compliance; the variability of development control non-compliance in the six quarters of Auchi was statistically significant, and the eta squared effect was also large. It was recommended that the town planning regulations be reassessed for a better practical effect; monitoring of developments to encourage compliance should be strengthened; and town planning manuals should be used to monitor and control developments.